Reliability of nucleotide sequence information of full-length flagellin A gene (flaA) and flaA short variable region (SVR) for molecular discrimination of Campylobacter lari organisms - Hirayama, J; Tazumi, A; Nakanishi, S; Tasaki, E; Hayashi, K; Moore, J E; Ueno, H; Millar, B C; Kuribayashi, T; Matsuda, M (Folia microbiologica, 2011)
We aimed to clarify if the thermophilic Campylobacter lari organisms including urease-negative (UN) C. lari and urease-positive thermophilic Campylobacter (UPTC) can be differentiated at the species and/or subspecies levels by employing the full-length flaA gene and flaA short variable region (SVR) nucleotide sequence information or not. Thermophilic Campylobacter isolates (n = 45) including UN C. lari (n = 17), UPTC (n = 18), and Campylobacter jejuni (n = 10) were well discriminated at the isolate level by the unweighted pair group method using arithmetic means analysis and neighbor joining procedures constructed based on the full-length flaA gene and flaA SVR nucleotide sequence information. Thus, these procedures may possibly be useful for epidemimological studies for C. lari and C. jejuni.
Keywords: Campylobacter lari; Animals; Genotype; flagelin; DNA bakterií; DNA, Bacterial; shluková analýza; lidé; Molecular Sequence Data; genotyp; Campylobacter jejuni; molekulární sekvence - údaje; polymorfismus genetický; Sequence Analysis, DNA; Flagellin; zvířata; sekvenční analýza DNA; Cluster Analysis; Polymorphism, Genetic; Humans